Trans-basin Atlantic-Pacific connections further weakened by common model Pacific mean SST biases - Chen Li (Nature Portfolio, 2020)
Many climate models failed to reproduce the eastern Pacific cooling that has been linked to slower warming in the early 20th century. Here, the authors present a feedback mechanism between the tropical Pacific and the Atlantic which contributes to this bias as it further dampens the Pacific cooling response in models.